Decreased homoserine levels in metabolic syndrome. Issue 4 (July 2020) - Patel, Ajay; Abdelmalek, Lillian; Thompson, Austin; Jialal, Ishwarlal
Abstract: Background and aims: The pathogenesis Metabolic Syndrome (MetS), a common global problem, remains to be elucidated. As part of our exploratory metabolomics research we determined if homoserine levels are an early biomarker of nascent MetS. Methods: An exploratory study involving 28 patients with nascent MetS and 20 matched controls. Metabolites were studied from early morning urine samples and assayed by the NIH Western Metabolomics Center using gas chromatography time-of-flight mass spectrometry and were standardized to urine creatinine. All of the patients enrolled in the study had normal renal and hepatic function. Results: Patients with MetS had statistically significant increases in overall waist circumference, blood pressure, glucose, HOMA-IR, HbA1C in comparison to the control group. Additionally, increases in IL-1b, IL-6, TLR-4, endotoxin, and leptin were also seen in the MetS group subjects compared to the control group. The concentrations of homoserine were significantly decreased 3-fold in patients with MetS in comparison to the matched controls, p = 0.0027. Furthermore, levels of homoserine were inversely correlated to multiple biomarkers of inflammation and cardio-metabolic risk factors such as HbA1C, blood pressure, TLR-4, leptin, endotoxin, and SAT secreted fetuin A. In addition, homoserine was positively correlated with lysine and NAT. Conclusions: In conclusion, low levels of homoserine could potentially contribute to the proinflammatory state in MetS. Highlights: MetS is a common global problem with an unknown aetiology. Metabolomics appear to offer some insights into its pathogenesis. Homoserine levels are significantly decreased in MetS and correlate with both inflammation and cardio-metabolic features.